Extraintestinal Manifestations of Crohn’s Disease in the Form of Pulmonary Nodules: A Case Report - Garg, Chandi (Cureus, 2020)
Crohn's disease is a systemic illness with a plethora of extraintestinal manifestations affecting various organs, of which the lungs are relatively rare. Pulmonary involvement may include airway diseases, lung parenchymal diseases, pleural diseases, or drug-related diseases. Tracheobronchial involvement is the most common respiratory presentation, whereas Crohn's disease-related interstitial lung disease is seen less frequently. A 41-year-old woman with a past medical history of Crohn's disease (status-post subtotal colectomy) presented to the hospital for an enlarging ground-glass opacity in her right middle lobe detected on routine computed tomography of the abdomen six months earlier. The opacity had increased in size from 21 x 18 mm to 28 x 18 mm and another ground-glass opacity in the right lower lobe increased in size from 5 mm to 12.4 mm. A robotic right middle lobectomy with lymph node dissection was done and bronchoscopy showed benign nodular lymphoid hyperplasia and a single perivascular epithelioid granuloma. A year later, her relapsing episodes of cough and shortness of breath were managed with prednisone, 20 mg, for a probable pulmonary manifestation of Crohn's disease. A non-contrast computed tomography of the chest showed interval resolution of the right lower lobe ground-glass opacity. A year after that, she presented to the hospital with increasing cough, shortness of breath, and a new right lower lobe ground-glass opacity (14 x 14 mm) on non-contrast computed tomography of the chest and has been managed with steroids with consideration of immunosuppression. In conclusion, pulmonary manifestations of Crohn's disease present in a myriad of varieties and often present confounding diagnostic problems necessitating an extensive work-up. Thus, Crohn's disease should be kept in the differential list in case of unusual clinical symptoms and radiological signs of idiopathic pulmonary presentations. These infrequent, and sometimes life-threatening, extraintestinal manifestations need to be considered when dealing with Crohn's disease to avoid further impairment of health status and alleviate patient symptoms by prompt recognition and treatment.